Identification of a new calcitonin gene in the salmon Oncorhynchus gorbuscha. - Jansz, H (1996)
Three isoforms of calcitonin (CT) exist in salmonids. Isohormones I and II are expressed in the pink salmon Oncorhynchus gorbuscha. We report here the existence in this species of a CT gene and of its transcripts, which encode for a fourth isohormone, the salmon CT (sCT) IV. This new CT gene was identified by PCR from genomic DNA and by sequencing the amplified DNA. The expression of this CT gene was established in ultimobranchial body and brain, by reverse transcription-PCR, hybridization and sequencing. The sCT IV gene, like the sCT I gene, is a complex transcription unit, containing exons encoding for a CT as a calcitonin gene-related peptide (CGRP) molecule. The predicted peptide, sCT IV, has a greater homology with the eel CT and the sCT II than with the sCT I. Alignment of the sCT IV with other fish and chicken CT showed amino acid modifications in similar positions as those found during evolution. The predicted salmon CGRP IV peptide is highly homologous to the known CGRP molecules in other species, confirming the high conservation of the molecule during evolution. This identification of a new salmon CT gene is interesting both for the therapeutic potential represented by the new molecules encoded by this gene and for phylogenetic studies.